Acromegaly: Beyond surgery. - Thanabalasingham, G; Grossman, AB (2013)
Acromegaly is characterized by chronic, excess secretion of growth hormone (GH) from a pituitary adenoma, and elevated hepatic insulin-like growth factor 1 (IGF-1) levels. Significant progress has been made in the development of medical therapies to achieve biochemical and symptomatic control in acromegaly. In this review we discuss the three currently available medical therapies, which include somatostatin analogs, dopamine agonists and pegvisomant. We describe a step-wise approach in which a somatostatin analog is followed by the addition of a dopamine agonist, and then if required the addition of or replacement by pegvisomant. New somatostatin agonists such as pasireotide, and the introduction of new orally-acting somatostatin agonists, should increase the therapeutic choices available in the near future.